Management of Difficult Airway Due to Chop Wound In Posterior Neck - Hazra, Rajdip; Chakraborty, Sisir; Bose, Rajarshi; SM, Manjunatha; Ghosh, Kaushik; Manuar, Md Babrak; Nurejjaman, Md; Pal, Saswati (International Journal of Medical and Health Sciences Research, 2014)
A 35 years old male patient presented with a chop wound in posterior neck between C2 and C3 interspace. After initial resuscitation this patient was put for surgery and general anesthesia was induced in left lateral position. Our experience suggested that a proper size ILMA (intubating laryngeal mask airway) is useful in managing difficult airway in left lateral position. Blind intubation attempt via ILMA is generally successful. We recommend routine use of ILMA as a backup plan in managing anticipated difficult intubation in nonconventional position.